2007
DOI: 10.1016/j.adolescence.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The involuntary treatment of adolescent psychiatric inpatients—A nation‐wide survey from Finland

Abstract: This national cross‐sectional study investigates the prevalence rates, regional differences and factors associated with the involuntary inpatient treatment of adolescents in Finland on a chosen day in 2000. The proportion of inpatients with involuntary legal status was 29.5% (n=82) giving a prevalence rate of 2.5 per 10,000/12–17 years old inhabitants.Forty‐eight per cent of involuntarily inpatients were 16–17 years old and 62% had psychotic disorders. Twenty‐six per cent of inpatients with involuntary legal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
3
20
1
Order By: Relevance
“…This finding might stem from high rates of involuntary treatment and legal detention in the Finnish adolescent psychiatric system (Kaltiala‐Heino 2004, Siponen et al . 2007, Ellilä et al . 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding might stem from high rates of involuntary treatment and legal detention in the Finnish adolescent psychiatric system (Kaltiala‐Heino 2004, Siponen et al . 2007, Ellilä et al . 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many in the field of adolescent psychiatry consider the use of containment measures to manage aggression in underage patients controversial (Bath 1994, Earle & Forquer 1995, Mesham 1995, Sourander et al . 2002, Ellilä et al . 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a risk that some adolescent patients lack or lose trust in parents and staff during hospitalization, and consequently feel isolated in the ward. Given frequent use of coercion, the potential for informal coercion, and the vulnerable adolescent years, perceived coercion in adolescents should be an important research topic [9].…”
Section: Opplysninger Fra Pasientadministrativt System -mentioning
confidence: 99%
“…Some prospective studies have connected experienced coercion to lower quality of life [ 12 ], and worse alliance and follow up of care [ 13 ], but a review found small or absent effects on variables such as psychosocial functioning, readmissions, or service engagement [ 14 ]. Given frequent use of formal coercion, the potential for informal pressure or coercion, and the vulnerable adolescent years, experienced coercion in adolescents should be an important research topic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%